Serum level of soluble interleukin 6 receptor is a useful biomarker for identification of treatment‐resistant major depressive disorder - Katsuhiko Yamasaki; Tomonori Hasegawa; Masatoshi Takeda (Wiley, 2020)
Abstract Aim A substantial proportion of major depressive disorder patients are treatment‐resistant to antidepressant therapy, who require augmentation drugs, or other treatments including electroconvulsive therapy or transcranial magnetic stimulation. Identifying treatment‐resistant major depressive disorder patients before the actual administration of antidepressant is, however, often difficult. Accordingly, the serum biomarker to identify treatment‐resistant patients will be helpful in clinical settings. This study aims to clarify the appropriate biomarkers for identification of treatment‐resistant major depressive disorder. Method Given that immune‐inflammatory processes are involved in the pathogenesis of major depressive disorder, it is possible that certain cytokine‐related molecules could serve as clinically useful biomarkers of treatment‐resistant major depressive disorder patients. In this study, we measured serum levels of tumor necrosis factor‐α, interleukin 6, and soluble interleukin 6 receptor after major depressive disorder patients underwent antidepressant therapy. Results The serum level of soluble interleukin 6 receptor, but not interleukin 6 or tumor necrosis factor‐α, was significantly higher in treatment‐resistant major depressive disorder patients than in remitted patients, suggesting that serum soluble interleukin 6 receptor could be a good biomarker of treatment‐resistant major depressive disorder. Receiver operating characteristic analysis confirmed that serum soluble interleukin‐6 receptor level measurement was useful for identification of treatment‐resistant major depressive disorder patients. Multiple regression analysis using the serum levels of the aforementioned cytokines as explanatory variables and the Quick Inventory of Depressive Symptomatology‐Self Report score (QIDS‐SR16) as a target variable showed that only serum soluble interleukin‐6 receptor level could explain the severity of major depressive disorder. Conclusion Based on these results, we recommend measurement of serum soluble interleukin‐6 receptor level to discriminate treatment‐resistant major depressive disorder patients. High serum soluble interleukin‐6 receptor level is associated with the pathogenesis of treatment‐resistant major depressive disorder, suggesting the involvement of the interleukin 6 trans‐signaling system in onset of treatment‐resistant major depressive disorder.